Commodity risk assessment of Citrus L. fruits from South Africa for Thaumatotibia leucotreta under a systems approach - EFSA Panel on Plant Health (PLH); Claude Bragard; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Juan A Navas‐Cortes; Stephen Parnell; Roel Potting; Philippe Lucien Reignault; et al. (EFSA Journal, 2021)
Abstract The European Commission requested to the EFSA Panel on Plant Health to evaluate a dossier from South Africa where the application of the systems approach to mitigate the risk of entry of the false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae), into the EU when trading citrus fruits is explained. After collecting additional evidence from the Department of Agriculture, Land Reform and Rural Development of South Africa, and reviewing the published literature, the Panel performed an assessment on the likelihood of pest freedom for T. leucotreta on citrus fruits at the point of entry in the EU considering the proposed systems approach. An expert judgement is given on the likelihood of pest freedom following the evaluation of the risk mitigation measures on T. leucotreta, including any uncertainties. There are three options (i.e. A, B and C) within the systems approach followed in South Africa that differentiate mainly in the sampling intensity in the field and the packing house as well as in temperature conditions during shipment. Therefore, three independent elicitations were conducted, one for each option. The main uncertainties were: (1) whether sampling once per orchard is representative for subsequent harvests (within 4 weeks) from the same orchard; (2) the correct implementation of the temperature regimes during shipment; (3) the mortality rate in fruit estimated for the different temperature regimes. The Expert Knowledge Elicitation indicated with 95% certainty that 9,182 out of 10,000 pallets for option A, 8,478 out of 10,000 pallets for option B, and 9,743 out of 10,000 pallets for option C will be free from T. leucotreta. In light of the additional information provided by South Africa once the elicitations were performed, it became apparent that the setting temperature during shipment was not achieved in 12 out of 14 cases of interceptions. Therefore, there is increased uncertainty on pest freedom. The Panel identified the weaknesses associated with the risk mitigation measures in the systems approach and made recommendations that could increase its effectiveness.